2015
DOI: 10.1097/qai.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report

Abstract: We analyzed georeferenced data on mobility and HIV infection from the 2009 Demographic and Health Survey of Lesotho. We found ~50% of the population traveled in the preceding year. By constructing gender-specific mobility maps we discovered travel is highest in the urban areas bordering South Africa, and in the mountainous interior of the country. For both genders, increased mobility was associated with increased levels of “recent” sexual behavior. Notably, mobility was only associated with an increased risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Temporary migration in Lesotho is related to employment; there is circular migration within the country to work in agriculture or the textile industry, and cross-border migration to work in the mines in South Africa. Previous studies of Lesotho have shown that (on average) residents who travel have higher numbers of sex partners than those who do not, and men who travel frequently have an increased risk of HIV infection (17). Permanent migration may also have facilitated the spatial diffusion of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary migration in Lesotho is related to employment; there is circular migration within the country to work in agriculture or the textile industry, and cross-border migration to work in the mines in South Africa. Previous studies of Lesotho have shown that (on average) residents who travel have higher numbers of sex partners than those who do not, and men who travel frequently have an increased risk of HIV infection (17). Permanent migration may also have facilitated the spatial diffusion of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a high risk of cross border importation of HIV infections from South Africa into the specific areas on the border that we have identified. Our previous research found travel was associated with an increased risk of HIV infection for men who traveled frequently 14 . Therefore these regions may be particularly suitable for interventions that target migrant workers and discordant couples; notably, there is a high level of discordancy (14%) in Lesotho 24 .…”
Section: Discussionmentioning
confidence: 92%
“…Individuals who change residency, either on a permanent or temporary basis, often maintain links with their home communities; this linkage can connect localized HIV epidemics 3 . Previous research has focused on individuals who travel, finding an association between mobility and increased sexual behavior, and between mobility and risk of HIV infection 4 5 6 7 8 9 10 11 12 13 14 . The effect of couple separation on the partner who stays at home and does not travel has received little attention; specifically, it is not known whether a partners’ absence increases the likelihood of having extramarital partners and subsequently the risk of HIV infection.…”
mentioning
confidence: 99%
“…Whilst these may appear obvious factors to include, statistical work continues to focus predominantly on the correlation between sexual behaviours and HIV prevalence and abstract categories of mobility (McGrath, et al, 2015;Palk and Blower 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst population mobility has played an important role in the historical spatial spread of the disease (Iliffe, 2006), linking geographically separate epidemics (Caldwell, Anarfi, & Caldwell, 1997;Tanser, Lesueur, Solarsh, & Wilkinson, 2000), current thinking within the health literature sees migrants as populations that are vulnerable to infection, engaging in higher levels of risky sexual behaviours than those who remain at home ( McGrath, Eaton, Newell and Hosegood 2015;Palk and Blower 2015;Schulyer et al, 2015). The standard narrative is that mobile individuals have sex while they are away from home for a range of reasons that include being separated temporarily from their spouses, and the enhanced opportunities for extra-marital sex that being away from home brings, and on return home transmit the virus to spouses or partners that have stayed behind (Deane, Johnston & Parkhurst 2013;Weine & Kashuba, 2012).…”
Section: Introductionmentioning
confidence: 99%